Traffic Stop Encounters: Officer and Citizen Race and Perceptions of Police Propriety - Huggins, Christopher M. (American journal of criminal justice, 2012)
The continued legacy of racism and discrimination contribute to racial and ethnic differences in attitudes about the police. This research investigates citizen reports of proper police behavior during traffic stops to understand how officer/citizen race and ethnic pairs influence reports of impropriety. Analysis of 6,301 citizen reports of traffic stop encounters with the police from a unique national survey reveals that net of other important explanatory variables, African-Americans are less likely than whites to report proper police behavior when they encounter officers of any race. In addition, citizen reports indicate that the white/black and black/white officer/citizen encounters are significantly less likely to result in a report of proper police behavior than the white/white officer/citizen pairing. The results show limited support for the importance of citizen race and officer/citizen pairs in determining perception of police behavior.